(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Fossil fuels are produced by non-renewable sources. The non-renewability is motivated for alternative fuels. Some common examples of feedstock for alternative fuels are seed oil, vegetable oil, waste cooking, soybean oil. Biodiesel is produced through transesterification reaction. Biodiesel production from waste cooking oil provides an alternate energy for various uses. Recycling waste cooking oil and methanol with the presence of (CaO) and (MgO) nano catalysts offers several benefits like economic, environmental and waste management. The nano catalysts CaO and MgO was synthesized by thermal decomposition method and calcinated at 500°C followed by characterization using diffraction (XRD) technique and RSM (Response Surface Methodology) is performed for optimization of the yield. This study investigates the repeatability of transesterification reaction with the presence of those nano catalysts.